The effectiveness of ozone therapy as a non-drug method for treatment of initial caries of permanent teeth in children - R.P. Oliynyk; M.M. Rozhko; V.S. Habchuk (Zaslavsky O.Yu., 2019)
Background. It is proved that the use of ozone will contribute to the growth of caries dental resistance, but the question about the adequacy of this method for the complete restoration of the already partly demineralized enamel structure remains controversial. Therefore, the purpose of our study was to determine the effectiveness of the isolated use of ozone for the treatment of initial caries of permanent teeth in children of different age groups (6, 12 and 15 years old). Materials and methods. We have performed treatment of initial caries with Ozone DTA/Ozonymed in 60 patients aged 6 to 15 years. CRT test was used to assess the structural resistance of enamel to the action of the acid factor. The enamel resistance to caries was determined using a modified enamel resistance of teeth test. The statistical processing of the study results was carried out in the Microsoft Excel 2017 software using arithmetic mean, arithmetic mean deviations, Pearson, Spearman and point-biserial correlation coefficients. Results. Results of the initial topographical distribution of caries lesions analysis showed a statistically higher (p ≤ 0.05) frequency of chewing teeth fissure defeat (36.67 %) compared with pathology of another localization. The sites of initial caries in 58.33 % of the examined persons were found on the upper jaw, in 46.67 % - on the lower. There was a decrease in the number of patients with a maximum and high risk of caries progression within a month of treatment - by 3.33 and 5.0 %, respectively. And three months later, the reduction in the number of patients with high risk of caries progression was documented (by 49.98 %). The finding indicate a positive ozone effect in terms of enamel resistance index increasing. However, none of the patients managed to achieve a complete reduction of carious spot, although a significant percentage of examined children noted a decrease in its size to those that statistically differed from the initial ones (p < 0.05). Conclusions. Feasibility of non-drug methods of initial caries treatment implementation was justified, however, the effectiveness of isolated ozone use is not enough.